2019
DOI: 10.1002/pen.25300
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Investigating Effect of Sulfur as a Coagent on the Quasi‐Static and Cyclic–Dynamic Fatigue Properties of Peroxide Cured EPDM

Abstract: The effect of sulfur on the quasi‐static and cyclic–dynamic fatigue properties of ethylene propylene diene monomer (EPDM) after three fatigue cycles were investigated under two specially designed test programs. The results turned out that sulfur as a coagent slowed down the vulcanization rate of EPDM compounds and reduced the chemical crosslinks. Further study on the effect of sulfur on the crosslinking behavior showed that this effect could be quantitatively described in linearity and became more distinct at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…15 Several mechanisms have been suggested to explain this effect and the most accepted one is the increase in tensile strength due to the greater mobility of polysulfidic bonds. 35 As reported by other studies, 36,37 the EP formulation showed the lowest tensile strength values compared to vulcanized systems with sulfur. This is attributed to the lower energy required to break peroxide-vulcanized rubber.…”
Section: Mechanical Propertiessupporting
confidence: 58%
“…15 Several mechanisms have been suggested to explain this effect and the most accepted one is the increase in tensile strength due to the greater mobility of polysulfidic bonds. 35 As reported by other studies, 36,37 the EP formulation showed the lowest tensile strength values compared to vulcanized systems with sulfur. This is attributed to the lower energy required to break peroxide-vulcanized rubber.…”
Section: Mechanical Propertiessupporting
confidence: 58%
“…Formation of crystallite zones near the crack tip results in branching of crack path along with the formation of micro‐cracks which triggers deviation from original crack path. [ 24 ] This deviation increases with ENR mol%. Formation of more deviated cracks stipulates the improvement of fracture resistance of ENR‐containing compounds.…”
Section: Resultsmentioning
confidence: 99%
“…For Figure 4B, further investigation has been made to correlate ( M H − M L ) with ν e value, and a linear relationship has been quantitatively obtained as follows, MnormalHMnormalL=1.6×νnormale+0.23R2=0.9282. One intercept value of ( M H − M L ) being 0.23 dNm has been obtained by extrapolating ν e to zero, indicating that the physical entanglement brings an initial torque. The initial torque is so low because the carbon black is difficult to disperse to increase the physical crosslinks through the rubber–filler interactions 19 …”
Section: Resultsmentioning
confidence: 99%
“…The initial torque is so low because the carbon black is difficult to disperse to increase the physical crosslinks through the rubber-filler interactions. 19…”
Section: Crosslink Densitymentioning
confidence: 99%